2010
DOI: 10.1542/peds.2009-2098
|View full text |Cite
|
Sign up to set email alerts
|

Migraine-Like Headache and Status Migrainosus as Attacks of Multiple Sclerosis in a Child

Abstract: The incidence of headache at the onset of relapsing-remitting pediatric multiple sclerosis (MS) is more frequent than in the adult MS population, but headache as the only symptom of a relapse, both in adults and children, is unusual. Here we describe the case of a 5-year-old child who developed MS and in whom migraine-like headache was the presenting symptom at both the onset of the disease and the following 2 relapses. Moreover, the first relapse was characterized by the occurrence of headache that fulfilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Multiple sclerosis (MS) is a chronic inflammatory disease producing demyelination and axonal damage in the brain and spinal cord 81. Pain is common in adults with a prevalence from 57% to 65%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS) is a chronic inflammatory disease producing demyelination and axonal damage in the brain and spinal cord 81. Pain is common in adults with a prevalence from 57% to 65%.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory symptoms were reported in 13%–69% of children with MS, but not the proportion with NP 82. Headache is more frequent than in adult patients with MS 81. The course of the disease may be slower in children, with higher rates of spontaneous recovery but it can still have a significant impact on schooling and quality of life 82…”
Section: Introductionmentioning
confidence: 99%
“…Both MS and migraines have a predilection for women as opposed to men. 8,9 In addition, both can come across as acute attacks on the body that negatively affect the ability of an individual to function. 9,10 That said, how is one supposed to differentiate the two as an associative concurrent affliction versus the primary causality of the other?…”
Section: Discussionmentioning
confidence: 99%
“…10 The relapsing-remitting attacks often include painful vision loss, diplopia, spasticity, weakness, numbness, tingling, or neurogenic bladder. 8 That said, migraines are not typically thought of as an "MS" symptom. Kister et al 15 was the first to suggest that migraines might be a presenting symptom of MS rather than just a concurrent nuisance.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported migraine-like headaches as the first presentation of MS attack. [11][12][13] Status migrainosus as a presenting symptom of MS is much rarer. 14 Herein, we report a case with status migrainosus as an MS attack with new T2 lesions and provide a comprehensive review of MS attacks presenting migraine headaches.…”
Section: Introductionmentioning
confidence: 99%